Penentuan Inside Information Dalam Praktek Insider Trading Di Pasar Modal Indonesia : Studi Perbandingan Dengan Perkara Texas Gulf Sulphur di Amerika Serikat - Ilham Rohjadina; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (USU LAW JOURNAL, 2019)
Abstract. Capital markets are seen as one way to accelerate the development of a country. The capital market is a business sector trading in securities such as stocks, stock and bond certificates. With the capital market companies will be easier to obtain funds, so that economic activities in various sectors can be increased. However, in the world of capital markets one of the problems faced is about insider trading. Insider trading is securities trading carried out by those who are classified as people in companies where securities trading is based on the existence of inside information that is important and contains material facts, where insider trading players expect economic benefits, directly or indirectly. The problems raised in this thesis are how to regulate the law and determine the inside information in the practice of insider trading in the Indonesian capital market with a comparative study on the case of Texas Gulf Sulfur in the United States. Based on these studies, the determination of insider trading in the case of Texas Gulf Sulfur in the United States is done by applying the theory of possibility. The foundation of the United States capital market law is contained in Rule 10b-5 concerning antifraud on the Securities and Exchange Act of 1934. Every transaction on the capital market gets protection and threats from Rule 10b-5. While the regulations governing insider trading in Indonesia are found in Articles 95, 96, 97 and 98 of Law No. 8 of 1995 concerning the Capital Market. According to these regulations, the qualifications of people in the capital market are listed companies or public companies and other companies that conduct transactions with the issuer or public company concerned. Insider trading is a practice done by a company (corporate insider) on stock trading by using information that contains material facts that it has and UUPM prohibits corporate insider.   Keywords: capital market, insider trading, inside information